Reducing acute stress disorders in mothers of leukemic children by means of the Family Centered Empowerment module (FACE) - Ilya Krisnana; Heny Sulistyarini; Praba Diyan Rachmawati; Yuni Sufyanti Arief; Iqlima Dwi Kurnia (University of Ostrava, 2019)
Aim: To analyze the effect of a parenting empowerment module, with the aim of reducing the stress experienced by the mothers of children suffering from leukemia. Design: The study used a quasi-experimental pre-test/post-test control group. Methods: The sample consisted of 60 mothers of leukemic children hospitalized in a pediatric oncology ward who met the inclusion criteria. The independent variable was the Family Centered Empowerment Module (FACE), which includes instruction on meeting nutritional needs, preventing infection, and preventing bleeding. The dependent variable was the stress experienced by mothers due to the hospitalization of their children. The instrument used for measuring stress of hospitalization was the DASS-21 questionnaire. The statistical tests used were Wilcoxon's signed rank test, and the Mann Whitney U Test (significance level α = 0.05). Results: There was a decrease in levels of stress in the intervention group (p = 0.001). In the control group there were differences in levels of stress both before and after treatment (p = 0.042). The results of the Mann Whitney U test indicated p = 0.017. Conclusion: Cognitive empowerment can improve the understanding of parents caring for leukemic children, and reduces the levels of stress associated with child hospitalization.